ANALISIS RASIO KEUANGAN TERHADAP KINERJA KEUANGAN PADA PT. HANJAYA MANDALA SAMPOERNA Tbk - Nita Oktaviani; Oktavianti Oktavianti; Catur Fatchu Ukhriyawati (University of Riau Kepulauan, 2014)
This study aims to determine the effect of simultaneous partial and Net Profit Margin (NPM) and Debt To Equity (DER) on Return On Equity (ROE) at PT. Hanjaya Mandala Sampoerna Tbk. There are two factors that can be used as a variable of independently the Net Profit Margin (NPM) and Debt To Equity (DER). While the dependent variable is the return To Equity (ROE).The data used in this study are secondary data from financial statements (ICMD and Annual Report) years from 2001 to 2011 are listed in the Indonesia Stock Exchange (IDX). While the method of data collection was done by purposive sampling method., Based on the method of the financial statements into the sample consists of 11 financial statements. This study uses multiple linear regression using the enter method, the results of this study show that the partial effect of independently variable on Return To Equity (ROE), the Net Profit Margin (NPM) with a value of 6,645 t count t table 2.306 and significant probability of 0 , 00 0.05 then the first hypothesis is accepted. And Debt To Equity (DER) also affect the Return To Equity (ROE), with a value of 2,985 t count t table 2.306 and significant probability value of 0.017 0.05 then the second hypothesis is accepted. While the simultaneous testing of independently variable effect on the dependent variable obtained 22 131 F count F table 4,459 with probability level of significance value of 0.001 0.05 then the third hypothesis is accepted.Value Coefficient of Determination shows that only 84.7% Return To Equity (ROE) PT. Hanjaya Mandala Sampoerna Tbk influenced By Net Profit Margin (NPM) and Debt To Equity (DER).